Morphological variation in cones and seeds of two species of pinyon pines distributed in a latitudinal gradient of Mexican highlands - Luna-Cavazos, Mario; Romero-Manzanares, Angélica; García-Moya, Edmundo (BOSQUE, 2025)
Intra and interpopulation variation of cones and seeds of Pinus cembroides and P. johannis from central Mexico was analyzed. Objectives: to identify cone and seed variation in two pinyon species; to corroborate taxa-specific identity according to cone and seed characteristics; and to detect genetic interaction between species. Cones and seeds were collected from 27 populations distributed in the Mexican Altiplano. Cone length and width, peduncle length, cone umbos length, number of scales, seed length and width, and testa thickness were measured. With the morphological characters, by population and between species, a univariate analysis was performed. Intra-population differences were analyzed with the Kruskal-Wallis test and interspecific differences with the t-test. Discriminant analysis was used to evaluate genetic interaction between species. Cone and seed morphometry between species showed significant differences in cone length and width, umbo length and seed length. P. johannis showed greater peduncle length and seed testa thickness. Discriminant analysis differentiated the two species and evidenced the eventual hybridization between them. The structures measured in populations of P. cembroides and P. johannis from the center of distribution had intermediate dimensions compared to northern or southern populations. The cones and seeds of P. cembroides were less variable than those of P. johannis in relation to latitudinal distribution. The information is considered useful for forest management and conservation of specific populations.